Development of a biobank in the structure of scientific and diagnostic and treatment institutions and prospects for interregional integration - R. S. Kalinin; O. V. Goleva; R. A. Illarionov; V. V. Tsai; A. L. Mukomolova; Yu. E. Konstantinova; I. V. Markin; A. V. Krylov; N. V. Rogozina; M. K. Bekhtereva; M. S. Tyan; E. D. Orlova; et al. (Кардиоваскулярная терапия и профилактика, 2022)
The formation of biobanks in the structure of scientific and treatment and diagnostic institutions with prospects for interregional integration is a fundamental link in monitoring and predicting diseases of various origins, creating and testing highly effective diagnostics, and developing novel therapeutic agents.Aim. To describe standard operating procedures and principles for the formation of bioresource collections (BRC) in medical institutions with biobanking.Material and methods. The data of scientific and practical biomedical projects using BRC obtained from patients with genetic, multifactorial and infectious diseases in St. Petersburg and Surgut are presented. As of September 2022, the BRC collected on the basis of the Pediatric Research and Clinical Center for Infectious Diseases of the Federal Medical and Biological Agency includes biosamples from 1619 patients, and the BRC collected in the Medical Institute of Surgut State University includes biosamples from 450 patients and healthy individuals of different sex and age. The selection of biosamples from apparently healthy individuals and patients with various diseases can serve as a strategically important resource for future research in terms of etiology, epidemiology, the development of regulatory environment and scales, innovations in the development of diagnostic approaches and treatment of the Russian population.